The Paradigmal Transition in General Economic Theory: The Role of Education (The Bulgarian Case) - Beev, Ivaylo (Research Papers, 2024)
This paper outlines the role of education in „paradigmal transitions“ (Kuhn's terminology) in theory and, in particular, the role of economics education in higher education for the economic paradigm shift (i.e. for a paradigmal transitions in economic theory). In a not-so-distant historical retrospective, in Bulgaria, such paradigmal transitions took place. Are the conditions for a new one present and what is the imperative change – these are questions whose answer presupposes the solution of the main task.
Keywords: General economic theory; Paradigm shift; Political economy; Economics; Education